Merkel Cell Carcinoma of the Head in a Young African Albino Woman with HIV/HTLV-1 Coinfection Associated with Multiple Squamous Cell Carcinomas - Daniela Tenea; Jurgen Dinkel; Jurgen C. Becker; Elisabeth van der Walt (Karger Publishers, 2019)
Merkel cell carcinoma (MCC) is a rare cutaneous neoplasm of presumed neuroendocrine origin, with aggressive behavior and poor prognosis, that tends to have an increased incidence among elderly Caucasians and immunosuppressed individuals. MCC is either associated with a clonal integration of the Merkel cell polyoma virus into the host genome or with genomic alterations caused by chronic UV exposure. Tumors of either carcinogenesis show epithelial, neuroendocrine, and B-lymphoid lineage markers. HIV-infected African albinos have a higher risk of developing skin cancers, including MCC, in comparison with the general population. We report a case of MCC of the head in a young albino woman with a HIV/HTLV-1 coinfection. The patient also suffered from multiple squamous cell carcinomas of the scalp, face, lip, and ears, suggesting an UV carcinogenesis of MCC. The purpose of this case report is to emphasize the relationship between immunosuppression (HIV/HTLV-1 coinfection, chronic sun exposure, ocular-cutaneous albinism, pregnancy) and MCC. It highlights the importance of early diagnosis, dermatological screening with a risk-stratified surveillance, particularly in immunosuppressed albino patients in sub-Saharan Africa, and multidisciplinary management of this biologically unique cutaneous cancer.